Asylum seekers and other precarious immigrants on the frontlines of the pandemic: Work experiences, resilience, resistance and social contributions - Salamanca Cardona, Manuel; Cleveland, Janet; Hanley, Jill (Alterstice)

(untitled) (Alterstice, 2022)
This article describes the labour conditions of asylum seekers and other precarious migrant workers before and during the pandemic. Although this group’s labour conditions were already precarious prior to the pandemic, we show how those conditions worsened during the COVID crisis because of their racialized condition and precarious migratory status. We also discuss the systemic impacts these negative conditions had on their personal lives, families and communities in spite of measures implemented by the provincial and federal governments. The article describes the resilience and resistance shown through the actions of grassroots community organizations, with immigrant and migrant members denouncing the hardships in their working environments and their community life. A mixed-methods research approach was used to collect and analyze both quantitative and qualitative data. The discussion and conclusions recognize the crucial social contributions of precarious immigrants, highlighting both their individual and political and collective resistance to their racialized condition and the negative effects they suffered during the pandemic.